Retroperitoneal liposarcoma excreting insulin‐like growth factor 2 that induced severe hypoglycemia. (24th December 2016) - Kato, Takuma; Sugimoto, Mikio; Yamashita, Motoki; Miyauchi, Yasuyuki; Hirama, Hiromi; Tsunemori, Hiroyuki; Ueda, Nobufumi; Imachi, Hitomi; Shibuya, Shinsuke; Kushida, Yoshio; Kakehi, Yoshiyuki
Abstract: Insulin‐like growth factor 2 is overexpressed in various cancers, and is associated with a poor prognosis. Also, it is known that insulin‐like growth factor 2 is an etiology of non‐islet cell tumor hypoglycemia. In this report, we describe a case of unexpected hypoglycemia caused by a dedifferentiated liposarcoma producing insulin‐like growth factor 2. A large mass in the retroperitoneum was detected in a 61‐year‐old man who complained of appetite loss. Despite having no history of diabetes mellitus, hypoglycemia suddenly occurred after admission, but oral glucose therapy was ineffective. After total parenteral nutrition, tumor resection was attempted, but failed as a result of rigid adhesion to the surrounding organs. The patient died of the disease 21 days after surgery. Pathological diagnosis at autopsy revealed dedifferentiated liposarcoma, and immunohistochemical staining showed that the tumor excreted insulin‐like growth factor 2. The possibility of an insulin‐like growth factor 2‐producing tumor should be taken into consideration when we encounter a patient with spontaneous hypoglycemia resistant to glucose substitution therapy.